2004
DOI: 10.1210/en.2003-1239
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Causes Decreased Osteoclastogenesis, Reduced Bone Formation, and Enhanced Apoptosis of Osteoblastic Cells in Bacteria Stimulated Bone Loss

Abstract: The most common cause of inflammatory bone loss is periodontal disease. After bacterial insult, inflammation induces bone resorption, which is followed by new reparative bone formation. Because diabetics have a higher incidence and more severe periodontitis, we examined mechanisms by which diabetes alters the response of bone to bacterial challenge. This was accomplished with db/db mice, which naturally develop type 2 diabetes. After inoculation of bacteria osteoclastogenesis and bone resorption was measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
165
0
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(181 citation statements)
references
References 40 publications
8
165
0
8
Order By: Relevance
“…The worsening of alveolar bone loss observed in diabetic animals with periodontal disease supporting previous studies, since there is a bidirectional relationship between these diseases (Breivik et al, 2005;Kim et al, 2012). In a research C57BL Db/db mice that developed diabetes at six to eight weeks of age to study decreased osteoclastogenesis in bacteria-stimulated bone loss (He et al, 2004). Jiang et al (2013) reported resorption values of alveolar bone in the upper second molar of four groups of rats at different time points.…”
Section: Bone Loss Is One Of the Complications In Diabetessupporting
confidence: 65%
“…The worsening of alveolar bone loss observed in diabetic animals with periodontal disease supporting previous studies, since there is a bidirectional relationship between these diseases (Breivik et al, 2005;Kim et al, 2012). In a research C57BL Db/db mice that developed diabetes at six to eight weeks of age to study decreased osteoclastogenesis in bacteria-stimulated bone loss (He et al, 2004). Jiang et al (2013) reported resorption values of alveolar bone in the upper second molar of four groups of rats at different time points.…”
Section: Bone Loss Is One Of the Complications In Diabetessupporting
confidence: 65%
“…Figure 3. www.bjournal.com.br bone, as reported in other diabetes models (6)(7)(8)(9)(10)(11)(12)(21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 56%
“…These include reduction in blood supply and angiogenesis (1), a more severe inflammatory response (18,19), a decrease in collagen synthesis (6,20,21), a disturbance in the mineralization process (9,11,12), and an imbalance between bone resorption by osteoclasts and bone deposition by osteoblasts (22)(23)(24). Another contributing factor may be the advanced glycation end products, present in high levels in diabetic individuals, that amplify inflammatory events (25) and delay wound healing (26).…”
Section: Introductionmentioning
confidence: 99%
“…To test whether AGEs stimulated apoptosis of bone-lining cells in vivo, CML-collagen and control collagen were injected adjacent to the scalp periosteum and apoptosis of periosteal cells was measured by the TUNEL assay as we have previously described (16). CML-collagen stimulated a 5 fold increase in apoptosis of these bone lining cells compared to unmodified collagen (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, premature aging caused by ablation of the klotho gene is associated with higher levels of osteoblast and osteocyte apoptosis (45). We have recently shown that diabetes causes enhanced apoptosis of osteoblastic cells following a bacterial stimulus (16). When apoptosis is inhibited there is a significant improvement in the capacity to form new bone demonstrating that diabetes-enhanced apoptosis is functionally important (5).…”
Section: Discussionmentioning
confidence: 99%